Literature Study of The Application of The Inquiry Learning Model Towards 21st Century Skills in Physics Subjects in High School - Milda, Debora; Anggreiny, Lavenia Puspa; Simanjuntak, Andrew; Lubis, Rajo Hasim (Lembaga Riset Mutiara Akbar, 2024)
In the 21st century as the century of industrial revolution 4.0. demands that all components in the school, starting from the principal, teachers, education staff and students, be directed to develop their competencies on an ongoing basis. Innovation is the most important key in the industrial era 4.0 which requires educators to form their students with 21st century competencies, namely being able to think critically, creatively, collaboratively and communicatively. This research aims to determine the effect of the inquiry-based learning model on improving students’ 21st century skills in physics subjects in high school. In the current era, learning is no longer just monotonous learning but prioritizes 21st century skills, namely critical thinking skills, creative skills, communication skills and collaboration skills. This research is library research whose data comes from library sources, namely library research. This article was written using a comparative study method and content analysis. Comparative literature studies are carried out by examining bold primary literature, such as journals, research reports, activity reports, books, magazines, news media, and other sources that meet validity and reputation standards. Analysis carried out on relevant articles proves that the application of inquiry has a positive impact on student learning activities. It is known from the results of this literature study that the application of the inquiry learning model in teaching and learning activities has a positive influence on students’ 21st century skills in physics subjects in high school, namely critical thinking skills, creative skills, communication skills and collaboration skills.